Increase in body mass index during the COVID-19 pandemic among people who smoke: An analysis of multi-site electronic health records. - R Constance Wiener; Christopher Waters; Emily Morgan; Patricia A Findley; Chan Shen; Hao Wang; Usha Sambamoorthi (Public Library of Science (PLoS), 2023)
The effects of the COVID-19 period among people who smoke (compared by sex) are largely unknown. The purpose of this study was to compare body mass index (BMI) increase among men and women who smoked during the pandemic. We used a retrospective longitudinal, observational study design of secondary data. We used electronic health records from TriNetX network (n = 486,072) from April 13, 2020-May 5, 2022 among adults aged 18-64 who smoked and had a normal BMI prior to the pandemic. The main measure was a change of BMI from < 25 to ≥25. Risk ratio was determined between men and women with propensity score matching. Overall, 15.8% increased BMI to ≥25; 44,540 (18.3%) were women and 32,341 (13.3%) were men (Risk Ratio = 1.38, 95% CI: 1.36, 1.40; p < .0001). Adults with diabetes, hypertension, asthma, COPD or emphysema or who were women, were more likely to develop BMI≥25 during the pandemic. Women who smoked were more likely to have an increase in BMI than men who smoked during the COVID-19 period.